Production, purification, and chemical characterization of Staphylococcus aureus exfoliative toxin. - Johnson, A D (1975)
Methods for the production and isolation of exfoliative toxin are described. Fermentation conditions were established under which large quantities of the crude material can be produced. Column chromatography methods, including carboxymethyl cellulose and hydroxyapatite, were utilized to purify the toxic protein. The pure toxin had a molecular weight of 26,000 as determined by polyacrylamide gel electrophoresis in sodium dodecyl sulfate. The pure toxin is a simple protein composed of 17 amino acids. Tests for carbohydrate and for alpha- and beta-hemolysin were negative. The mean effective dose of the purified toxin was 0.5 mug per newborn mouse.